2020
DOI: 10.3390/ijerph17051588
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Sociocognitive Process of Construction Workers’ Unsafe Behaviors: An Agent-Based Modeling Approach

Abstract: Previous literature has recognized that workers' unsafe behavior is the combined result of both isolated individual cognitive processes and their interaction with others. Based on the consideration of both individual cognitive factors and social organizational factors, this paper aims to develop an Agent-Based Modeling (ABM) approach to explore construction workers' sociocognitive processes under the interaction with managers, coworkers, and foremen. The developed model is applied to explore the causes of cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 90 publications
0
15
0
13
Order By: Relevance
“…It is widely accepted that the SB of construction workers is the crucial factor in safety management and this has been paid much attention to in previous studies [ 5 ]. The prior studies primarily focused on leadership behavior [ 111 , 112 ], safety culture and climate [ 113 , 114 ], safety attitudes [ 115 , 116 ] and safety norms [ 112 , 117 , 118 ]. However, limited consideration is paid to the importance of the reaction about an individual’s subject emotion to work like job satisfaction, especially in the construction industry.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that the SB of construction workers is the crucial factor in safety management and this has been paid much attention to in previous studies [ 5 ]. The prior studies primarily focused on leadership behavior [ 111 , 112 ], safety culture and climate [ 113 , 114 ], safety attitudes [ 115 , 116 ] and safety norms [ 112 , 117 , 118 ]. However, limited consideration is paid to the importance of the reaction about an individual’s subject emotion to work like job satisfaction, especially in the construction industry.…”
Section: Discussionmentioning
confidence: 99%
“…Construction activities were usually performed without using personal protective equipment for the respiratory tract and a study carried out in the Veneto Region evidenced a high lung content of asbestos fibers in various tasks [ 17 ]. An increasing number of studies demonstrated that the perception of occupational risks is influenced by a set of individual, social, cultural, and organizational variables [ 35 , 36 , 37 ]. Although it is common knowledge that asbestos is dangerous, many workers may be unaware of the actual degree of danger and the inherent risk situations [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 90 ] proposed an Agent-based construction safety-related behavior modeling method, which regarded safety performance as an emergency attribute of the behaviors and interaction of construction personnel and management team. Ye et al [ 91 ] developed an agent-based modeling method to explore the interaction of the social-cognitive process of construction workers with managers, colleagues and foremen. The authors also applied the developed model to explore the reasons for the cognitive failure of construction workers and the influence of social groups and social organization factors on workers’ unsafe behaviors [ 91 ].…”
Section: A State-of-the-art Review Of Related Literaturementioning
confidence: 99%
“…Ye et al [ 91 ] developed an agent-based modeling method to explore the interaction of the social-cognitive process of construction workers with managers, colleagues and foremen. The authors also applied the developed model to explore the reasons for the cognitive failure of construction workers and the influence of social groups and social organization factors on workers’ unsafe behaviors [ 91 ].…”
Section: A State-of-the-art Review Of Related Literaturementioning
confidence: 99%